PENGARUH STRUKTUR ASET MARKET VALUE ADDED PROFITABILITAS SERTA EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020-2022 - Olivia, Jesslyn; Budianto , Melvin; Sitorus, JessySafitri; Khanti Listya (Journal Accounting International Mount Hope, 2024)
This research aims to determine the influence of Asset Structure, Market Value Added, Return on Assets and Earnings Per Share on Share Prices in food and beverage sub-sector companies listed on the IDX in 2020-2022. This research uses quantitative data and the research population that will be used in the research is 30 companies in the food and beverage sub-sector listed on the IDX in 2020-2022 with a research sample of 63. Partial research results show that Asset Structure has a negative and significant influence on Share Prices, Market Value Added has a positive and significant influence on Share Prices, Return On Assets has a negative and significant influence on Share Prices, Earnings Per Share has a positive and significant influence on Share Prices and Asset Structure, Market Value Added, Return On Assets and Earnings Per Share have a positive and significant influence on Share Prices